LEGAL RECONSTRUCTION OF COPYRIGHT AS MARITAL PROPERTY IN INDONESIAN LAW - Piput Milandsari Milandsari; Yenny Eta Widyanti; Yuliati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the reconstruction of copyright law as marital property within the Indonesian legal framework, focusing on the economic rights of works created during marriage. The research background stems from the complexity of the relationship between intellectual property rights and family law, where copyright often becomes a source of conflict in asset division during divorce. Employing a normative method with legislative, comparative, and conceptual approaches, this study compares regulations in Indonesia and the People's Republic of China. The findings indicate that Indonesia lacks specific rules on the division of economic copyright rights as marital property, whereas China has explicitly integrated them into the Civil Code. Reconstruction is proposed through harmonization of the Copyright Law and Marriage Law, differentiation between moral and economic rights, and the establishment of technical regulations to ensure legal certainty, justice, and protection of creators' rights. These findings contribute to the development of a more responsive national law towards intangible assets in family contexts.